Analysis of the effects of caffeine and dioxidine on biochemical indicators of blood in mouse - N. A. Durnova; A. S. Sheremetyeva; A. Yu. Karetnikova (RUDN Journal of Medicine, 2021)
Relevance . In connection with the widespread use of caffeine, an important issue is the study of its interaction with substances that can exhibit toxic effects. Objective. The aim of the study is to assess the degree of influence of caffeine and dioxidine on the biochemical parameters of blood in mice in the forced swimming test. Materials and methods. The studies were carried out on 6 groups of male mice: control and five experimental. During 15 days of the experiment, the animals of the control group were injected with physiological saline, and the experimental animals were injected with caffeine at a dose of 40 mg/kg or 100 mg/kg (1 and 2), dioxidine in an amount of 200 mg/kg (3), and caffeine was combined and dioxidine (4 and 5). Biochemical parameters were used to determine the content of glucose, cholesterol, urea, creatinine, the activity of aspartic and alanine aminotransferases. Results . The introduction of caffeine at a dose of 40 mg/kg led to a decrease in glucose levels below normal and an increase in cholesterol and urea concentrations. The use of caffeine at a dose of 100 mg/ kg caused a decrease in glucose levels below normal and an increase in urea concentration. With the introduction of dioxidine at a dose of 200 mg/kg, an increase in the level of glucose, cholesterol, urea, as well as the activity of AST and ALT was taken. The combined use of caffeine and dioxidine by the 15th day led to 100 % mortality in experimental animals. Conclusions . The results of the experiment indicate that the introduction of caffeine at a dose of 40 mg/kg and 100 mg/kg leads to an increase in most of the measured parameters relative to the control values, but they do not go beyond normal values, however, a decrease in glucose levels is noted. These changes in indicators are due to the predominance of catabolic processes over anabolic ones. In animals treated with dioxidine, a significant increase in the concentration of metabolites and the activity of blood enzymes was found, especially an increase in AST and ALT was noted, which indicates a predominant lesion of cardiomyocytes. The mortality rate of the experimental groups receiving caffeine and dioxidine together by the last day of the experiment is due to the action of an excessive stress factor leading to the depletion of the adaptive capabilities of the organism and the death of experimental animals.